Effect of Blinding and Unmasking on the Quality of Peer Review - van Rooyen, Susan (Blackwell Science Inc, 1999)
The objectives of this study were to see whether, in the opinion of authors, blinding or unmasking or a combination of the two affects the quality of reviews and to compare authors' and editors' assessments. In a trial conducted in the British Medical Journal, 527 consecutive manuscripts were randomized into one of three groups, and each was sent to two reviewers, who were randomized to receive a blinded or an unblinded copy of the manuscript. Review quality was assessed by two editors and the corresponding author. There was no significant difference in assessment between groups or between editors and authors. Reviews recommending publication were scored more highly than those recommending rejection.